The control theory manager : combining the control theory of William Glasser with the wisdom of W. Edwards Deming to explain both what quality is and what lead-managers do to achieve it /: combining the control theory of William Glasser with the wisdom of W. Edwards Deming to explain both what quality is and what lead-managers do to achieve it. (1995) - Unknown
No abstract available